2010
DOI: 10.1016/j.bmcl.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of 1,2,4-triazolo[1,5-c]pyrimidine derivatives as A2A receptor-selective antagonists

Abstract: Movement disorders such as Parkinson's disease and Huntington's disease are serious life-limiting and debilitating movement disorders. Their onset typically occurs from mid-life to late in life, and effective diagnostic techniques for detecting and following the disease course are lacking. Our goal is to develop receptor imaging agents for positron emission tomography (PET) that selectively target the most relevant subtype of adenosine receptors (AR) that are highly expressed in the striatum, i.e. the A 2A AR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 20 publications
(17 reference statements)
3
39
0
Order By: Relevance
“…For glucocorticoid-and/or cAMP-inducible genes, real-time polymerase chain reaction analysis of cDNA was performed using the primer sequences shown in Todde et al (2000), which is 82-times lower than that found by Shinkre et al (2010). These reactions were performed using a StepOnePlus instrument (Applied Biosystems) on 2.5 ml of cDNA in 10-ml reactions using Fast SYBR Green chemistry (Invitrogen) according to the manufacturer's guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…For glucocorticoid-and/or cAMP-inducible genes, real-time polymerase chain reaction analysis of cDNA was performed using the primer sequences shown in Todde et al (2000), which is 82-times lower than that found by Shinkre et al (2010). These reactions were performed using a StepOnePlus instrument (Applied Biosystems) on 2.5 ml of cDNA in 10-ml reactions using Fast SYBR Green chemistry (Invitrogen) according to the manufacturer's guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro metabolism evaluation was conducted in cryopreserved rat hepatocytes with analysis of the generated metabolites by HPLC-MS [32]. Authentic non-radioactive MRS5425 (7-(3-(4-(2-fluoroethoxy)phenyl)propyl)-2-(furan-2-yl)-7H-pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidin-5-amine), was prepared as previously described [33]. …”
Section: Methodsmentioning
confidence: 99%
“…Values are expressed as the mean ± SEM. ND, not determined. b Data from Shinkre et al [14] and Kecskes et al [19]. …”
Section: Figures and Tablementioning
confidence: 99%
“…the A 2A AR, we developed a O -(3-fluoropropyl) analogue, intended for incorporation of 18 F. It was essential to identify an insensitive position on 2 that would accommodate a chain. The methoxy group of the phenyl ring of 2 was selected for this purpose because it has been shown to display flexibility of substitution and conformation with respect to binding to the A 2A AR, as deduced from structure activity relationship (SAR) studies in conjunction with molecular modeling and ligand docking [14]. …”
mentioning
confidence: 99%
See 1 more Smart Citation